Pencarian lokasi gym di Malang menggunakan metode simple additive weighting: studi kasus di Institut Asia Malang - Prasetyo, Bima; Riska, Suastika Yulia (Jurnal Ilmiah Teknologi Informasi Asia, 2025)
The main problem in this research is the large selection of gyms in Malang Raya with various different criteria, which makes the process of selecting the right gym difficult for prospective users. This research aims to develop the best gym location recommendation system in Malang Raya using the Simple Additive Weighting (SAW) method. The SAW method is used to evaluate gyms based on the main criteria, namely price, facilities, cleanliness, mentoring system, and distance. Data collected through surveys and observations was then analyzed using SAW to produce a ranking of gyms in the region. The results showed that Momon Gym ranked first with the highest score, while WWGYM ranked last. Tests comparing the actual ranking results with the results from the computer program using the SAW method showed high consistency, indicating that the method is reliable in providing objective recommendations. This research also shows that SAW is effective in analyzing multi-criteria data for more accurate and efficient decision-making in selecting gyms that match users' preferences.